2015
DOI: 10.1016/j.gca.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and oxygen isotope composition of main-group pallasites and olivine-rich clasts in mesosiderites: Implications for the “Great Dunite Shortage” and HED-mesosiderite connection

Abstract: International audienceEvidence from iron meteorites indicates that a large number of differentiated planetesimals formed early in Solar System history. These bodies should have had well-developed olivine-rich mantles and consequentially such materials ought to be abundant both as asteroids and meteorites, which they are not. To investigate this "Great Dunite Shortage" we have undertaken a geochemical and oxygen isotope study of main-group pallasites and dunitic rocks from mesosiderites.Oxygen isotope analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 88 publications
10
71
2
Order By: Relevance
“…Measurements of Fukang's metal and olivine phases are consistent with a Main‐group pallasite classification; this is in agreement with a prior oxygen isotope study that demonstrated Fukang's Main‐group affinity (Greenwood et al. ). However, Fukang exhibits small but important inclusions not yet observed in other Main‐group pallasites.…”
Section: Introductionsupporting
confidence: 88%
“…Measurements of Fukang's metal and olivine phases are consistent with a Main‐group pallasite classification; this is in agreement with a prior oxygen isotope study that demonstrated Fukang's Main‐group affinity (Greenwood et al. ). However, Fukang exhibits small but important inclusions not yet observed in other Main‐group pallasites.…”
Section: Introductionsupporting
confidence: 88%
“…The first possibility is unlikely because enstatite chondrites, which are the best analogs for the parent materials to aubrites, have much more heterogeneous ∆ 17 O values [from -0.32 to +0.16 ‰ for twelve EH3-6 chondrites, and from -0.11 to +0.07 ‰ for sixteen EL3-6 chondrites taken into account only falls and HCl treated finds (Newton et al, 2000)]. Moreover, the level of ∆ 17 O homogeneity shown by the aubrite falls (± 0.010 ‰ (2σ)) is equivalent to that of other bodies which show evidence for an early global stage of melting i.e., 4-Vesta [± 0.014 ‰ (2σ), Greenwood et al, 2005Greenwood et al, , 2014Scott et al, 2009], the angrite-parent body [± 0.014 ‰ (2σ), Greenwood et al, 2005], the main-group pallasites parent body [± 0.016 ‰ (2σ), Greenwood et al, 2006Greenwood et al, , 2015, the Moon [< ± 0.021 ‰ (2σ), Spicuzza et al, 2007;Hallis et al, 2010;Herwartz et al, 2014;Young et al, 2016] and Mars [± 0.026 ‰ (2σ), Franchi et al, 1999]. Thus, the narrow range of oxygen isotope compositions displayed by the aubrites indicates that some form of isotopic homogenization took place on their parent body.…”
Section: Evidence For Early Large-scale Melting On the Aubrite Parenmentioning
confidence: 67%
“…), HEDs (2σ and 3σ from Greenwood et al. , , ), the anomalous howardite JaH 556 (Janots et al. ), and various anomalous basaltic achondrites (Greenwood et al.…”
Section: Resultsmentioning
confidence: 99%